Tinjauan Yuridis Tindak Pidana Kepemilikan Narkotika Oleh Anak Di Bawah Umur (Studi Putusan No. 56/Pid.Sus-Anak/2021/PN Mks) - Sitti Harlina; Asrul Aswar; Alief Rifky Sugiarto (Pledoi Law Jurnal, 2024)
ABSTRACT: This research aims to find out how material criminal law is applied to perpetrators of criminal acts of possession of narcotics by minors and what the legal considerations of judges are in handing down decisions against perpetrators of criminal acts of possession of narcotics by minors. This research is Normative Juridical legal research, using a literature study approach using qualitative methods. The research results show (1) The application of material criminal law to perpetrators of the crime of possession of narcotics by minors has been fulfilled, including the elements of every person, without the right to control, and those who commit, order to commit and who participate in committing the act. (2) Judges' legal considerations in imposing criminal sanctions on perpetrators are still not appropriate, they should take more into account the child's future by providing diversion for child defendants. ABSTRAK: Penelitian ini bertujuan mengetahui Bagaimanakah penerapan hukum pidana materil terhadap pelaku tindak pidana kepemilikan narkotika anak di bawah umur dan Bagaimanakah pertimbangan hukum hakim dalam menjatuhkan putusan terhadap pelaku tindak pidana kepemilikan narkotika oleh anak di bawah umur. Penelitian ini merupakan penelitian hukum Normatif Yuridis, melalui pendekatan studi kepustakaan yang menggunakan metode kualitatif. Hasil penelitian menunjukkan (1) Penerapan hukum pidana materil terhadap pelaku tindak pidana kepemilikan narkotika anak di bawah umur telah terpenuhi diantaranya unsur setiap orang, tanpa hak menguasai, dan mereka yang melakukan, menyuruh melakukan dan yang turut serta melakukan perbuatan. (2) Pertimbangan hukum Hakim dalam menjatuhkan sanksi pidana terhadap pelaku masih kurang tepat seharusnya lebih mempertimbangkan masa depan anak dengan memberikan diversi terhadap terdakwa anak.